How to choose a partner - Quilliam, Susan, ....- (London : Macmillan, 2016)
Choosing a romantic partner is one of contemporary life's biggest adventures. But other aspects of modern living - being globally more mobile, a fall in religious belief, social liberalization and more job opportunities (but longer working hours) - mean meeting a mate has rarely been so challenging, and rarely so important. In How to Choose a Partner, Susan Quilliam guides us through the process of finding the right partner for us as individuals. The real challenge is that we grow. Drawing upon rich cultural material, psychology and her background in relationship therapy, Susan presents partner choice as a self-development journey, driving us to learn more about ourselves, about other people, about life and the way we want to live.
Keywords: Partnerkeuze